2018
DOI: 10.1371/journal.pone.0198027
|View full text |Cite
|
Sign up to set email alerts
|

β2-microglobulin induces depressive- and anxiety-like behaviors in rat

Abstract: β2-microglobulin (B2M), the light chain of major histocompatibility complex class I (MHC I) molecules, has been found to impair hippocampal neurogenesis. Based on the crucial role of hippocampal neurogenesis disturbance in the process of depression and anxiety, the aim of the present study is to investigate whether B2M leads to depressive- and anxiety-like behaviors. We found that 6 days after intracerebroventricular injection with B2M (0.3 μg), the immobility times of rats in the tail suspension test and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In copper hub, the expression B2M protein encoding gene with the copper concentration showed negative correlation which suggests that the decreased copper concentration increases the B2M gene expression in PD. Increased B2M has been observed in patients with Alzheimer’s disease 28 dementia 29 , Parkinson’s diseases 30 , and Schizophrenia patients 31 . Also, Zhang et al showed B2M induced rat causes cognitive impairments, depression, and anxiety that are closely linked with Parkinson’s disease symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In copper hub, the expression B2M protein encoding gene with the copper concentration showed negative correlation which suggests that the decreased copper concentration increases the B2M gene expression in PD. Increased B2M has been observed in patients with Alzheimer’s disease 28 dementia 29 , Parkinson’s diseases 30 , and Schizophrenia patients 31 . Also, Zhang et al showed B2M induced rat causes cognitive impairments, depression, and anxiety that are closely linked with Parkinson’s disease symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…After feeding initiation (or after 10min), rats were removed from the chamber and returned to the homecage where post-test consumption of pre-weighed Froot loops was recorded for 10min. Post-test consumption was used as a measure of appetite (Iijima et al, 2012;Zhang et al, 2018). 2.5 Thermal Sensitivity Testing (Hargreaves Test) Rats were assessed for thermal sensitivity using the Plantar Analgesia Meter (IITC).…”
Section: Methodsmentioning
confidence: 99%
“…The climbing bar time was determined immediately when the physical strength of the mouse was exhausted. 15 The forced swimming test was carried out as described previously. Briefly, 30 min after the final treatments, mice were placed individually in a swimming pool filled with water (25 ± 1°C) to a depth of 30 cm with a lead sheath (5% of the mouse's body weight) attached to the tail root of each mouse.…”
Section: Animals and Treatmentmentioning
confidence: 99%